Improvement of HbA1c in type 2 diabetes mellitus patients by supplementation of mixed herbs - Mahmood, Tahir; Ali Khan Khattak, Muhammad Muzaffar; Mohd Shukri, Nor Azwani (2019)
Liver is the central organ of the body where all the absorbed compounds including the dietary components, drugs are dispatched for further metabolism. This action of liver causes altered production of enzymes. In medical practice particularly when dealing with lowering of blood lipids in type 2 diabetes (T2DM) patients it is essential to assess the liver function test. The aim of this study was to assess the effect of mixed herbs on the liver function tests and blood HbA1c in T2DM patients. In this study we examined the effect of four herbs in T2DM patients. Freshly purchased herbs were cleaned, freeze-dried, ground, mixed (25% of each herb), encapsulated and 4g were fed to the T2DM patients for 90 days. Blood samples were collected at day 0, 31, 61, 91 & 121. The effect was assessed on the HbA1c and creatinine, blood urea concentration. The liver enzymes i.e. Alanine Transaminase (ALT) or serum glutamic-pyruvic transaminase (SGPT), Aspartate aminotransferase (AST) or serum glutamic-oxaloacetic transaminase (SGOT), Alkaline phosphatase (ALP) concentration among the patients. The data was statistical analysed and the differences in the means was regarded as significant at 95% confidence interval. The HbA1c was highest on day 0 & 31 and significantly (p<0.001 & p<0.01) lower on the day 61, 91 and 121. Creatinine concentration was highest on day 61 and followed by day 91, 121. The blood urea concentration in the blood was not affected due to the larger variation among the subjects. The ALT and AST concentration was higher (p<0.001) at day 61 and started to decline afterwards. The concentration of ALP was higher on the day 0 & 31 and started declining from day 61 onwards. Apparently, the consumption of mixed herbs was associated with an improvement of HbA1c in the T2DM patients.